2012
DOI: 10.2495/safe-v2-n2-145-166
|View full text |Cite
|
Sign up to set email alerts
|

A mining project is a field of risks: a systematic and preliminary portrait of mining risks

Abstract: Due to the current economic situation and the growth in world demand, the mining industry is undergoing a period of spectacular development. The current need to increase production at mine sites coincides with the development of managerial capacities, the use of new industrial methods and equipment, and increased use of skilled workforce. Despite such developments, a number of researchers view the mining sector among the world's most uncertain and hazardous industries. Although the sector utilizes risk managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…They then constructed a conceptual model of an approach previously proposed [29] using general research hypotheses, on the basis of the principal elements of the challenge as described above (Section 3). As they progressed, they adapted and improved the reference model through action research involving both industrial partners [6,7,30]. In doing so, they evaluated the conceptual model developed by gathering and using data and assessing the improvements.…”
Section: Implementation and Results: The Case Of Two Goldmines In Quementioning
confidence: 99%
See 3 more Smart Citations
“…They then constructed a conceptual model of an approach previously proposed [29] using general research hypotheses, on the basis of the principal elements of the challenge as described above (Section 3). As they progressed, they adapted and improved the reference model through action research involving both industrial partners [6,7,30]. In doing so, they evaluated the conceptual model developed by gathering and using data and assessing the improvements.…”
Section: Implementation and Results: The Case Of Two Goldmines In Quementioning
confidence: 99%
“…The importance of identifying OHS risks associated with industrial projects and adequate planning of their management was thus demonstrated. The researchers then added the perspective of the mining industry and exposed the importance of systematic integration of OHS into the management of projects in this sector [6,7,29,30]. The need for innovative solutions adapted to allow OHS risks to be taken into consideration throughout the project lifecycle was thus demonstrated.…”
Section: Implementation and Results: The Case Of Two Goldmines In Quementioning
confidence: 99%
See 2 more Smart Citations
“…The life cycle of a mining project generally consists of four phases: exploration (F1), development (F2), operation (exploitation) (F3) and closure (F4) [2].…”
Section: Life Cycle Of the Mining Projectmentioning
confidence: 99%